Substrate and TGV through hole glass suitable for semiconductor packaging field and preparation method of substrate and TGV through hole glass
The micro-nano texture structure is formed by floating glass molding and plasma treatment, and then modified silicon carbide fibers are sprayed and cured with a pulsed CO2 laser. This solves the problem of insufficient interface adhesion during copper plating of glass substrates, and achieves high adhesion and high light transmittance adhesion high alumina silicon glass.
Patent Information
- Application Number
- CN202411749447.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
The existing glass substrates lack interfacial adhesion during copper plating, resulting in the metal layer being easily shedding, affecting the signal quality, and the surface treatment method will affect the transparency of the glass.
High-aluminum silicon matrix glass is prepared by floating glass molding process, and a micro-nano texture structure is formed through plasma technology. After spraying the nanoliquid of modified silicon carbide fibers, the whole piece is scanned and cured using a pulsed CO2 laser to form adhesion high-aluminum silicon glass.
It improves the interface adhesion and light transmittance of the glass, ensures the stability of the metal copper plating, improves product quality, and maintains high light transmittance and excellent mechanical properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass, and more specifically, to a substrate and TGV through-hole glass suitable for the field of semiconductor packaging and a preparation method thereof. Background Art
[0002] Glass substrates are widely used in semiconductor devices. The excellent large-size stability of glass substrates realizes the basic rules of precision redistribution layer (RDL) similar to the back-end process (BEOL), and also facilitates precise metallization; the customizable coefficient of thermal expansion (CTE) of glass makes it suitable for excellent small-pitch assembly technology; this makes glass an attractive material in 5G radio frequency (RF) front-end equipment manufacturing and heterogeneous packaging applications.
[0003] Glass core substrate is the key to determine the performance of millimeter wave devices, and usually requires the material to have good stiffness, chemical stability, weather resistance, high resistivity and low high-frequency dielectric loss. In traditional solutions, substrate materials such as low-temperature co-fired ceramics and polymers have limitations in technology, cost and supply. Borosilicate glass has higher resistivity, lower dielectric loss and dielectric constant than silicon, as well as a coefficient of thermal expansion (CTE) that matches the device and good rigidity. It can be used to manufacture thinner and less rough substrates for large-size wafer / panel packaging.
[0004] The through-glass via (TGV) process is simple and does not require the deposition of an insulating layer; large-size glass substrates are easy to obtain, have strong mechanical stability, small warpage, and low cost. Due to the excellent electrical properties of glass substrates, TGV technology has been widely used in RF components, optoelectronic integration, and micro-electromechanical systems (MEMS).
[0005] In glass through-hole technology, there are strict requirements for the performance of glass substrates. The glass substrate first needs to have high light transmittance and low absorption to ensure that the light can maintain sufficient brightness and clarity when passing through the glass. At the same time, the glass substrate should also have excellent mechanical strength and chemical stability to withstand various stresses and environmental changes during processing. More importantly, in the process of large-size wafer / panel packaging, it is usually necessary to plate copper on the surface of the glass substrate to improve the conductivity and heat conduction efficiency, especially in some high-frequency and high-speed application scenarios. However, due to the smooth surface of the glass substrate itself, the adhesion to copper is low, which can easily cause the metal layer to fall off, curl, etc. In the prior art, a surface treatment liquid containing surfactants, cross-linking agents, composite leveling agents, etc. (or directly adding similar components to the copper plating liquid) is usually used to treat the surface of the glass substrate before copper plating to improve its interface adhesion. However, after treatment by this method, although the adhesion is improved, it will affect the overall transparency of the glass substrate, thereby affecting the signal quality. Summary of the invention
[0006] In order to solve the above problems, the present application provides a substrate and TGV through-hole glass applicable to the field of semiconductor packaging and a preparation method thereof.
[0007] This application adopts the following technical solutions:
[0008] In a first aspect, the present application provides a method for preparing a substrate and a TGV through-hole glass applicable to the field of semiconductor packaging, which comprises:
[0009] (1) preparing raw materials according to the following formula in terms of molar percentage of oxides: SiO2 52-73%, Al2O3 10-25%, B2O3 4-25%, MgO 0.5-8%, SrO 2-8%, CaO 1-9%, BaO 0.1-7%, ZrO2 0.1-1%, Fe2O3 0.3-5%, and clarifier 0.1-2%;
[0010] (2) A glass substrate obtained by a float glass forming process is annealed in an atmosphere containing SO2, and then chemically strengthened to obtain a high-aluminum-silicon substrate glass;
[0011] (3) The high-alumina-silicon substrate glass is treated with plasma technology. After a micro-nano texture structure is formed on any surface of the high-alumina-silicon substrate glass, a nano-liquid containing modified silicon carbide fibers is sprayed on the surface. After heating and curing, a pulsed CO2 laser is used to scan the entire surface to form an adhesive high-alumina-silicon glass.
[0012] Furthermore, when the pulsed CO2 laser is used for scanning, the spot width is 0.3-0.5 mm, the scanning frequency is 100-200 Hz, and the output power of the CO2 laser is 40-50 W.
[0013] Furthermore, the concentration of the modified silicon carbide fiber in the nanofluid is 4-6wt%, and the solvent is ethanol.
[0014] Furthermore, the modified silicon carbide fiber is obtained by the following preparation method:
[0015] Dispersing (N-methylperfluorohexylsulfonamido)ethyl acrylate and 2-hydroxy-4-methoxybenzophenone in an organic solvent, and uniformly mixing by ultrasonication to obtain a modified solution;
[0016] Silicon carbide fiber is added to the modified solution, and then a catalytic amount of metal palladium is added, and the obtained solution is placed in a heated environment for stirring and reaction to obtain modified silicon carbide fiber.
[0017] Furthermore, in the above process of preparing the modified silicon carbide fiber, the reaction temperature is 70-90° C., the reaction time is 12-18 hours, and the stirring frequency is 200-500 rpm.
[0018] Furthermore, in the above-mentioned modified liquid, the mass ratio of the silicon carbide fiber, the ethyl acrylate (N-methylperfluorohexylsulfonamide) and 2-hydroxy-4-methoxybenzophenone is 1:0.2-0.3:0.05-0.15.
[0019] Furthermore, the parameters of the plasma technology used to treat the high-aluminum-silicon substrate glass are: argon is used as the working gas, the flow rate is 6-8 L / min, the voltage is 50-60 KV, and the frequency is 70-80 Hz.
[0020] Furthermore, the composition of the above-mentioned adhesive high-alumina-silicate glass in terms of molar percentage of oxides satisfies the following conditions: SiO2+Al2O3 is 70-80%.
[0021] In a second aspect, the present application provides a substrate and TGV through-hole glass suitable for the field of semiconductor packaging, which are obtained by the above-mentioned preparation method.
[0022] Furthermore, the dielectric constant of the glass is 6-7, the transition point temperature is greater than 600°C, and the expansion coefficient is 30×10 -7 / ℃-50×10 -7 / ℃, the transmittance at 550nm wavelength is greater than or equal to 96%, and the surface adhesion is 25-27Mpa.
[0023] In summary, this application has the following beneficial effects:
[0024] 1. This application improves the comprehensive performance of glass in all aspects by optimizing the formula and preparation process of glass, so that it has excellent dielectric constant and expansion coefficient, and has a high operating temperature, with a transition point of >600°C. More importantly, this glass retains extremely strong light transmittance while having strong interface adhesion through surface treatment on the strengthened base glass, and the transmittance at a wavelength of 550nm is greater than or equal to 96%. These properties enable the glass to be used as a substrate for large-size wafer / panel packaging, and can be further copper-plated in glass through-hole technology. Due to its excellent interface adhesion and very small light scattering, it can improve the stability of the metal copper coating, thereby improving product quality.
[0025] 2. When the substrate glass is subjected to surface treatment, the present application first uses plasma technology to treat the substrate glass. Since the plasma contains a large number of ions, excited molecules, free radicals and other active ions, it can interact with the substrate glass surface during high-speed motion, so that the glass surface forms a micro-nano texture structure, which increases the specific surface area of the glass and introduces functional groups such as hydroxyl and amino groups on the glass surface; and since the contact angle of the treated glass surface is smaller than the smooth surface before treatment, the wettability of the glass is enhanced, which is more conducive to the subsequent curing of silicon carbide fibers. Subsequently, a nanofluid containing modified silicon carbide fibers is sprayed, and a pulsed CO2 laser is used for scanning and curing, which can form a uniform and dense adhesion layer on the glass film, thereby reducing the surface energy of the glass and enhancing the interfacial adhesion without affecting the light transmittance.
[0026] 3. In a preferred embodiment of the present application, the silicon carbide fiber is modified by using ethyl acrylate (N-methylperfluorohexylsulfonamide) and 2-hydroxy-4-methoxybenzophenone to be grafted with a fluorine-containing polymer. When it is subsequently scanned with a pulsed CO2 laser, the instantaneous high heat output of the laser causes the fluorine-containing polymer grafted on the silicon carbide fiber to bond with the active groups generated on the glass surface due to plasma treatment, forming a network cross-linked structure on the glass surface, which greatly improves the surface adhesion. DETAILED DESCRIPTION
[0027] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0028] The substrate and TGV through-hole glass provided in this embodiment are applicable to the field of semiconductor packaging, and include the following components in terms of molar percentage of oxides:
[0029] SiO2 52~73%, Al2O3 10~25%, B2O3 4~25%, MgO 0.5~8%, SrO 2~8%, CaO 1~9.9%, BaO 0.1~7%, ZrO2 0.1~1%, Fe2O3 0.3~5%, clarifier 0.1~2%;
[0030] Wherein, the clarifier includes SO4 2- 、NO3 - 、F - , Cl - , SnO2, Sb2O3 or more.
[0031] SiO2 is the main component that forms silicon-oxygen tetrahedrons and connects to form a glass network structure, and is the basic skeleton of glass. The amount of SiO2 added is 52-73%, preferably 54-68%. For example, in terms of molar percentage of oxide, SiO2 accounts for 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, etc. of high-alumina silicate glass.
[0032] When SiO2<52%, the chemical resistance of glass is poor, and the surface state of glass deteriorates after acid and alkali corrosion. The higher the SiO2 content, the greater the degree of interconnection between silicon-oxygen tetrahedrons, and the higher the chemical stability of glass. When SiO2>72%, the high-temperature viscosity of glass increases, and the melting temperature increases sharply, which is not conducive to production. Therefore, it is necessary to control its content within an appropriate range.
[0033] Al2O3 is easy to form tetrahedral coordination, and [AlO4] tetrahedral coordination can help build a tighter network with [SiO4] tetrahedrons. It is an important component of the glass network structure, which can also make the geometric shape of the glass change slightly. The amount of Al2O3 added is 10-25%, preferably 12-18%. For example, in terms of molar percentage of oxide, Al2O3 accounts for 10%, 11%, 12%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, etc. of high-alumina silicate glass. When the Al2O3 content is higher than 13%. However, when the Al2O3 content exceeds 25%, it is easy to cause the glass to become foggy or even devitrified. In addition, it will increase the high-temperature viscosity, increase the difficulty of melting, and be unfavorable for production.
[0034] MgO can relax the relationship between temperature and viscosity and reduce the phenomenon of glass devitrification. It can improve the glass solubility, strain point and Young's modulus, reduce the crystallization tendency and crystallization speed, increase the high temperature viscosity of the glass, and improve the chemical stability and mechanical strength of the glass. However, when the MgO content is too high, it will also increase the surface tension of the glass, resulting in melting difficulties. The content of MgO in the glass of the present invention ranges from 0.05-8%, preferably 2-6%. For example, MgO accounts for 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, etc. of the high alumina silicate glass in terms of molar percentage of oxide.
[0035] CaO can improve the chemical stability of glass, increase the mechanical strength and hardness of glass, and adjust the thermal expansion coefficient. The content of CaO in the glass of the present invention ranges from 1 to 9%. For example, in terms of molar percentage of oxide, CaO accounts for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc. of high alumina silicate glass.
[0036] BaO is a divalent network exometallic oxide that can increase the refractive index, density, gloss and chemical stability of glass. A small amount of BaO can accelerate the melting of glass, but when the content is too much, secondary bubbles will appear in the clarification. The content of BaO in the glass of the present invention ranges from 0.1 to 7%. For example, in terms of molar percentage of oxide, BaO accounts for 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, etc. of high alumina silicate glass.
[0037] SrO is a network-external oxide, and its effect on glass is between that of CaO and BaO. The content of SrO in the glass of the present invention ranges from 2 to 8%. For example, in terms of molar percentage of oxide, SrO accounts for 2%, 3%, 4%, 5%, 6%, 8%, etc. of the high-alumina-silica glass.
[0038] B2O3 is generally a colorless, transparent, hard and brittle substance (can scratch glass), with a density of 1.84 g / cm 3 , melting point 600℃. Density of crystalline boron oxide 1.805g / cm 3 , melting point 295℃, boiling point 1860℃, soluble in water and alcohol, strong water absorption, often exists as a glass network former. B2O3 often exists in glass in two structures [BO4] and [BO3]. When the glass contains enough free oxygen, boron participates in the network structure in the form of [BO4] and plays a role in connecting the network. [BO4] is a tetrahedral structure. When it exists, it can reduce the tendency of glass crystallization, increase the refractive index of glass, improve the gloss, and improve chemical stability and heat resistance; when the content of the glass component network is low and cannot provide enough free oxygen, boron exists in the form of [BO3] triangle and does not enter the glass network. [BO3] is a chain and layered structure. If it is gradually increased, the glass will have a lower softening temperature, poorer chemical stability and a larger expansion coefficient. The structures of [BO4] and [BO3] transform into each other, and the glass will show obvious changes in certain properties. Glass science calls it boron anomaly, that is, the maximum or minimum appears on the component and property curve. The boron anomaly can be used to make the glass meet certain specific requirements. Excessive boron content in the glass component will lead to serious boron volatilization, and cause problems such as unstable glass components and environmental pollution. The present invention limits the B2O3 content to 4-25%, preferably 9-21%. Exemplarily, in terms of molar percentage of oxide, B2O3 accounts for 4%, 5%, 8%, 9%, 10%, 12%, 18%, 20%, 21%, 23%, 25%, etc. of the high alumina silicate glass.
[0039] ZrO2 not only has the best water resistance and acid resistance, but also has the best alkali resistance. An appropriate amount of ZrO2 helps to improve the chemical durability and hardness of the glass. However, if too much ZrO2 is contained, on the one hand, the resistance to devitrification of the glass will decrease, and on the other hand, the meltability will deteriorate and there will be a tendency to devitrification, making molding difficult. The content of ZrO2 in the glass of the present invention ranges from 0.1 to 1%. For example, in terms of molar percentage of oxide, ZrO2 accounts for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 0.9%, 1%, etc. of the high alumina silicate glass.
[0040] The transmittance of the adhesive high aluminosilicate glass finally obtained in the present application to a wavelength of 550nm is greater than or equal to 96%. The transmittance of the high aluminosilicate glass can be used for substrates and TGV through-hole glasses suitable for the semiconductor packaging field. The transmittance is measured by using a spectrophotometer with reference to the standard ISO13468-1:1996.
[0041] The expansion coefficient of the adhesive high alumina silicate glass finally obtained in this application is 30×10 -7 / ℃~50×10 -7 / ℃. The expansion coefficient of high alumina silicate glass can be used for the thermal expansion coefficient of substrates and TGV through-hole glass suitable for semiconductor packaging (α20 / 300℃) and the data of 20~300℃ is tested according to the method specified in GB / T7962.16-2010.
[0042] The dielectric constant of the adhesive high-alumina silicate glass finally obtained in the present application is 6-7.
[0043] The transition point of the finally obtained adhesive high alumina silicate glass of the present application is greater than 600° C. The transition point of high alumina silicate glass can be used for substrates and TGV through-hole glass in the field of semiconductor packaging. The transition temperature (Tg) is tested according to the method specified in GB / T7962.16-2010.
[0044] The hardness of the adhesive high alumina silicate glass was measured by using a Vickers hardness tester with reference to the standard GB / T16534-2009.
[0045] The density (ρ) of adhesive high alumina silicate glass is tested according to the method specified in GB / T7962.20-2010.
[0046] Adhesion The surface adhesion of high alumina silicate glass is tested according to the method specified in GB / T 5210-2006.
[0047] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0048] Example of preparation of raw materials
[0049] Preparation Example 1
[0050] This preparation example provides a modified silicon carbide fiber, which is prepared by the following method:
[0051] (1) dispersing 24 g of (N-methylperfluorohexylsulfonamido)ethyl acrylate and 7.6 g of 2-hydroxy-4-methoxybenzophenone in 200 ml of ethylene glycol, and mixing them by ultrasonication to obtain a modified solution;
[0052] (2) Add 100 g of silicon carbide fiber (50-100 nm) to the modified solution, then add a catalytic amount of metal palladium, place the resulting solution in a heating environment and stir to react, the heating temperature is 78°C, the stirring frequency is 300 rpm, the reaction time is 15 h, and then wash the resulting material with 0.1 M HCl and water in turn until neutral, and after freeze-drying, obtain modified silicon carbide fiber.
[0053] Preparation Example 2
[0054] This preparation example provides a modified silicon carbide fiber, which is prepared by the following method:
[0055] (1) Dispersing 20.47 g of (N-methylperfluorohexylsulfonamido)ethyl acrylate and 5.13 g of 2-hydroxy-4-methoxybenzophenone in 200 ml of ethylene glycol, and mixing by ultrasonication to obtain a modified solution;
[0056] (2) Add 100 g of silicon carbide fiber (50-100 nm) to the modified solution, then add a catalytic amount of metal palladium, place the resulting solution in a heating environment and stir to react, the heating temperature is 90°C, the stirring frequency is 200 rpm, and the reaction time is 12 h. Then, wash the resulting material with 0.1 M HCl and water in turn until it is neutral, and after freeze-drying, obtain modified silicon carbide fiber.
[0057] Preparation Example 3
[0058] This preparation example provides a modified silicon carbide fiber, which is prepared by the following method:
[0059] (1) Dispersing 28.31 g of (N-methylperfluorohexylsulfonamido)ethyl acrylate and 13.06 g of 2-hydroxy-4-methoxybenzophenone in 200 ml of ethylene glycol, and mixing by ultrasonication to obtain a modified solution;
[0060] (2) Add 100 g of silicon carbide fiber (50-100 nm) to the modified solution, and then add a catalytic amount of metal palladium. Place the resulting solution in a heating environment and stir to react. The heating temperature is 70°C, the stirring frequency is 500 rpm, and the reaction time is 12 h. Then, wash the resulting material with 0.1 M HCl and water in turn until it is neutral. After freeze-drying, modified silicon carbide fiber is obtained.
[0061] Preparation Example 4
[0062] This preparation example provides a modified silicon carbide fiber, which is prepared by the following method:
[0063] (1) dispersing 24 g of ethyl (N-methylperfluorohexylsulfonamido) acrylate in 200 ml of ethylene glycol, and mixing by ultrasonication to obtain a modified solution;
[0064] (2) Add 100 g of silicon carbide fiber (50-100 nm) to the modified solution, then add a catalytic amount of metal palladium, place the resulting solution in a heating environment and stir to react, the heating temperature is 78°C, the stirring frequency is 300 rpm, the reaction time is 15 h, and then wash the resulting material with 0.1 M HCl and water in turn until neutral, and after freeze-drying, obtain modified silicon carbide fiber.
[0065] Example
[0066] Example 1
[0067] This embodiment provides a substrate and TGV through-hole glass applicable to the field of semiconductor packaging, and the preparation method thereof is as follows:
[0068] (1) Prepare the materials according to the mass ratio of each oxide in Table 1, and add cullet powder and clarifier to prepare the finished batch material. Melt, clarify and shape the finished batch material.
[0069] (2) using a float glass forming process to melt, clarify and form the finished batch material to obtain a glass matrix; passing the glass matrix through an annealing furnace containing an SO2 atmosphere at a uniform speed for annealing;
[0070] (3) After preheating the annealed glass substrate, the glass substrate is placed in a molten salt for two chemical strengthenings. The first chemical strengthening salt bath is 100% NaNO3, and the strengthening conditions are: 440°C, 80 min; the second chemical strengthening salt bath is a mixed salt of 98% KNO3 and 2% NaNO3, and the strengthening conditions are: 420°C, 90 min, to obtain a high aluminum silicon substrate glass;
[0071] (4) Plasma technology was used to treat the surface of high-aluminum-silicon substrate glass with argon as the working gas, a flow rate of 7 L / min, a voltage of 54 KV, and a frequency of 76 Hz;
[0072] (5) Using ethanol as solvent, adding 60 g of modified silicon carbide fiber (60-100 nm) provided in Preparation Example 1, stirring evenly, to obtain a nanofluid with a mass concentration of 5 wt%;
[0073] (6) The nanofluid obtained in step (5) is sprayed onto the surface of the high-aluminum-silicon substrate glass obtained in step (4), and after low-temperature drying at 64° C., the entire piece is scanned using a pulsed CO2 laser. The scanning spot width is 0.38 mm, the scanning frequency is 160 Hz, and the output power of the CO2 laser is 48 W, thereby obtaining an adhesive high-aluminum-silicon glass.
[0074] Embodiment 2-6
[0075] The difference between this group of embodiments and embodiment 1 is that the ratio of oxides is different, as shown in Table 1:
[0076] Table 1.
[0077]
[0078]
[0079] As can be seen from Table 1, the glass substrate provided by the present application has a dielectric constant of 6-7, a transition point temperature greater than 600°C and a maximum temperature of 854°C, and an expansion coefficient of 30×10 -7 / ℃-50×10 -7 / ℃, the transmittance of 550nm wavelength is greater than or equal to 96%, the surface adhesion is 25-27Mpa, and it has good acid and water resistance, and can be very useful in the field of semiconductor packaging and TGV through-hole technology.
[0080] Example 7
[0081] The difference between this embodiment and embodiment 1 is that in step (4), the parameters of the plasma treatment are different, specifically: argon is used as the working gas, the flow rate is 6L / min, the voltage is 60KV, and the frequency is 80Hz to treat the surface of the high-aluminum-silicon substrate glass.
[0082] Example 8
[0083] The difference between this embodiment and embodiment 1 is that in step (4), the parameters of the plasma treatment are different, specifically: argon is used as the working gas, the flow rate is 8L / min, the voltage is 50KV, and the frequency is 70Hz to treat the surface of the high-aluminum-silicon substrate glass.
[0084] Example 9
[0085] The difference between this embodiment and embodiment 1 is that in step (5), different modified liquid is used. Specifically, ethanol is used as solvent, 60 g of modified silicon carbide fiber (60-100 nm) provided in preparation example 2 is added, and after stirring evenly, a nano liquid with a mass concentration of 4 wt % is obtained;
[0086] Example 10
[0087] The difference between this embodiment and embodiment 1 is that in step (5), different modified liquid is used. Specifically, ethanol is used as solvent, 60 g of modified silicon carbide fiber (60-100 nm) provided in preparation example 3 is added, and after stirring evenly, a nano liquid with a mass concentration of 6 wt % is obtained;
[0088] Embodiment 11
[0089] The difference between this embodiment and embodiment 1 is that in step (6), the parameters of the laser scanning are different. Specifically: after low-temperature drying, a pulsed CO2 laser is used to scan the entire sheet. The scanning spot width is 0.5 mm, the scanning frequency is 100 Hz, and the output power of the CO2 laser is 40 W, thereby obtaining high-adhesion aluminum silicate glass.
[0090] Example 12
[0091] The difference between this embodiment and embodiment 1 is that in step (6), the parameters of the laser scanning are different. Specifically: after low-temperature drying, a pulsed CO2 laser is used to scan the entire sheet. The scanning spot width is 0.3 mm, the scanning frequency is 200 Hz, and the output power of the CO2 laser is 50 W, thereby obtaining high-adhesion aluminum silicate glass.
[0092] Comparative Example
[0093] Comparative Example 1
[0094] The difference between this comparative example and Example 1 is that the high-alumina-silicon substrate glass obtained in step (3) is not subjected to subsequent treatment;
[0095] Comparative Example 2
[0096] The difference between this comparative example and Example 1 is that before spraying the nanofluid, step (4) is not used to perform plasma treatment on the surface of the high-aluminum-silicon substrate glass.
[0097] Comparative Example 3
[0098] The difference between this comparative example and Example 1 is that the nanofluid contains ordinary unmodified silicon carbide fibers (5wt%, 60-100nm).
[0099] Comparative Example 4
[0100] The difference between this comparative example and Example 1 is that the modified silicon carbide fiber contained in the nanofluid is provided by Preparation Example 4.
[0101] Comparative Example 5
[0102] The difference between this comparative example and Example 1 is that when curing the nanofluid, a continuous wave laser is used to scan the entire sheet, the spot width is 0.38 mm, and the scanning frequency is 160 Hz.
[0103] Performance Testing
[0104] The standard test methods described in the embodiments were used to test various properties of the glass substrates provided in Example 1 and Comparative Examples 1-5. The results are shown in Table 2:
[0105] Table 2.
[0106]
[0107] As can be seen from Table 2, compared with Example 1, since Comparative Example 1 did not perform subsequent plasma treatment and modified silicon carbide fiber treatment on the obtained high-aluminum silicon matrix glass, the surface of the final product obtained was smooth and the surface adhesion was low. In Comparative Example 2, plasma treatment was not used before the modified silicon carbide fiber treatment. Although other properties of the final product were not greatly affected, the surface adhesion was significantly reduced, which shows that plasma treatment can significantly enhance the treatment effect of subsequent modified silicon carbide fibers. Comparative Example 3 uses unmodified silicon carbide fibers for treatment. Although the surface adhesion is enhanced compared to the high-aluminum silicon matrix glass of Comparative Example 1, it is still weaker than Example 1 of the present application, and the light transmittance is also weakened to a certain extent. This shows that modifying silicon carbide fibers is very critical for improving the light transmittance and surface adhesion of the product. Similarly, in Comparative Example 4, although the silicon carbide fibers are modified to a certain extent, the effect obtained is also weak because the modification method is not the optimal method. In Example 5, due to the use of a continuous wave laser for scanning, the curing film-forming effect of the modified silicon carbide fiber is poor, resulting in unsatisfactory light transmittance and surface adhesion of the product.
[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a substrate and TGV through-hole glass suitable for the field of semiconductor packaging, characterized in that: It includes: Prepare the raw materials according to the following formula in terms of molar percentage of oxides: SiO2 52-73%, Al2O3 10-25%, B2O3 4-25%, MgO 0.5-8%, SrO 2-8%, CaO 1-9%, BaO 0.1-7%, ZrO2 0.1-1%, Fe2O3 0.3-5%, clarifier 0.1-2%; A glass substrate is obtained by a float glass forming process, the glass substrate is annealed in an atmosphere containing SO2, and then chemically strengthened to obtain a high-aluminum-silicon substrate glass; The high-alumina-silicon matrix glass is treated with plasma technology. After a micro-nano texture structure is formed on any surface of the high-alumina-silicon matrix glass, a nano-liquid containing modified silicon carbide fibers is sprayed. After heating and curing, a pulsed CO2 laser is used to scan the entire piece to form an adhesive high-alumina-silicon glass.
2. The method for preparing a substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 1, characterized in that: When the pulsed CO2 laser is used for scanning, the spot width is 0.3-0.5 mm, the scanning frequency is 100-200 Hz, and the output power of the CO2 laser is 40-50 W.
3. The method for preparing a substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 1, characterized in that: The concentration of the modified silicon carbide fiber in the nanofluid is 4-6wt%, and the solvent is ethanol.
4. The method for preparing a substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 1, characterized in that: The modified silicon carbide fiber is obtained by the following preparation method: Dispersing (N-methylperfluorohexylsulfonamido)ethyl acrylate and 2-hydroxy-4-methoxybenzophenone in an organic solvent, and uniformly mixing by ultrasonication to obtain a modified solution; Silicon carbide fiber is added to the modified solution, and then a catalytic amount of metal palladium is added, and the obtained solution is placed in a heated environment for stirring and reaction to obtain modified silicon carbide fiber.
5. The method for preparing a substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 4, characterized in that: In the process of preparing the modified silicon carbide fiber, the reaction temperature is 70-90° C., the reaction time is 12-18 hours, and the stirring frequency is 200-500 rpm.
6. The method for preparing a substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 4, characterized in that: In the modified liquid, the mass ratio of the silicon carbide fiber, the ethyl acrylate (N-methylperfluorohexylsulfonamide) and 2-hydroxy-4-methoxybenzophenone is 1:0.2-0.3:0.05-0.
15.
7. The method for preparing a substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 1, characterized in that: The parameters for treating the high-aluminum-silicon substrate glass with plasma technology are: argon is used as the working gas, the flow rate is 6-8 L / min, the voltage is 50-60 KV, and the frequency is 70-80 Hz.
8. The method for preparing a substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 1, characterized in that: The composition of the adhesive high-alumina silicate glass in terms of molar percentage of oxides satisfies the following conditions: SiO2+Al2O3 is 70-80%.
9. A substrate and TGV through-hole glass suitable for the field of semiconductor packaging, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 8.
10. The substrate and TGV through-hole glass suitable for the semiconductor packaging field according to claim 9, characterized in that: The glass has a dielectric constant of 6-7, a transition point temperature greater than 600°C, and an expansion coefficient of 30×10 -7 / ℃-50×10 -7 / ℃, the transmittance at 550nm wavelength is greater than or equal to 96%, and the surface adhesion is 25-27Mpa.